Strategi Kepemimpinan Kepala Sekolah Terhadap Peran Guru dan Orang Tua dalam Meningkatkan Mutu Pendidikan Karakter di Gugus SD Negeri Blang Bintang Kabupaten Aceh Besar - Zulkhaidir, Zulkhaidir; Musdiani, Musdiani; Kasmini, Lili (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the planning and strategies carried out by school principals regarding the role of teachers and parents in improving the quality of character education in the Blang Bintang State Elementary School Cluster, Aceh Besar Regency. This research method is qualitative with a descriptive approach. The subjects of this research were school principals, teachers and parents of students in the Blang Bintang State Elementary School cluster. Research data analysis is carried out with descriptive qualitative techniques through data reduction, data presentation, and conclusion drawing. The results of the research show that the principal's leadership strategy regarding the role of teachers and parents in improving the quality of character education in the Blang Bintang State Elementary School cluster is to plan various programs involving teachers and parents of students. The teacher's role is implemented in several forms of training activities such as increasing teacher competency related to educational character, comparative studies to other schools, providing opportunities to take courses, carrying out activities through teaching, modeling, strengthening and habituation. . Meanwhile, the principal's leadership strategy regarding the role of parents is carried out by building synergy through a personal and persuasive approach